Survival Rate and Growth of Acropora sp. Transplanted on Artificial Substrate in Kampung Ambong, Likupang Timur - Antou, Kevin J. P.; Rondonuwu, Ari B.; Moningkey, Ruddy D. (Jurnal Ilmiah Platax, 2019)
60 coral specimens transplanted on three artificial substrates, namely bamboo, iron and concrete showed that the average length of coral fragments on the bamboo substrate for four months ranged from (7.45 - 10.11 cm) the highest increase in the highest coral length occurred in the second month (1.05 cm). On the average iron substrate, the average coral fragment length ranged (9.41 - 11.68 cm), the absolute increase in coral length was highest in the fourth month (0.94 cm). Whereas on the concrete substrate (5.23 - 6.77 cm) on the concrete substrate the absolute increase was highest in the third month (0.73 cm). The results of data analysis showed the rate of increase in coral Acropora sp. ranged (0.50 - 0.78 cm / month, on the bamboo substrate the rate of increase showed a better value of the iron and concrete substrate which was equal to (0.78 cm / month). In this study the survival of corals had a percentage that could be said to be successful. iron survival rate of 90% and on the concrete substrate by 70%.Keywords: Acropora sp, TransplantationABSTRAK60 spesimen karang yang ditransplantasi pada tiga substrat buatan yaitu bambu, besi dan beton menunjukkan bahwa rataan panjang fragmen karang pada substrat bambu selama empat bulan diperoleh berkisar (7,45 - 10,11 cm) pertambahan mutlak panjang karang tertinggi terjadi pada bulan kedua yaitu (1,05 cm). Pada substrat besi rataan panjang fragmen karang rata – rata berkisar (9,41 – 11.68 cm) pertambahan mutlak panjang karang tertinggi pada bulan keempat yaitu (0.94 cm). Sedangkan pada substrat beton (5,23 – 6,77 cm) pada substrat beton pertambahan mutlak tertinggi pada bulan ketiga (0,73 cm). Hasil analisis data menunjukkan laju pertambahan karang Acropora sp. berkisar (0.50 – 0.78 cm/bulan, pada substrat bambu laju pertambahan menunjukkan nilai yang lebih baik dari substrat besi dan beton yaitu sebesar (0.78 cm/bln). Dalam penelitian ini keberhasilan hidup karang mempunyai persentase yang bisa dikatakan berhasil. Pada substrat bambu dan besi tingkat kelangsungan hidup sebesar 90% dan pada substrat beton sebesar 70%.Kata Kunci : Acropora sp, Transplantasi